Gambaran Persepsi Mahasiswa terhadap Pemenuhan Fungsi Media Pembelajaran pada Kartu Anatomi Gigi (Kabanogi) - Shofiati Try Handayani (FKG 16 UMY 156, 2016)
Background : Kartu Anatomi Gigi (Kabanogi) is kind of inovation in active learning media which contains pictures and the explanations about the dental morphology. Kabanogi can be used by dentistry students to support the learning process of teeth anatomy. The reason why the researcher decided make this media was due to the difficulty of dental students of 2014 class in Muhammadiyah University of Yogyakarta to learn and memorize the teeth anatomy, especially for the specific characteristics of the dentition morphology. Kabanogi, as one of learning media, should fulfill the functions and can be accepted by the dentistry students. Objective : The objective of the study is to find out the student’s perception of learning media fulfillmet in Kabanogi. Method: Types of this research was descriptive observational and the design was cross sectional. Samples were 53 dental students class of 2014 Muhammadiyah University of Yogyakarta who were taken by quote sampling. The instruments were Kartu Anatomi Gigi (Kabanogi) and questionnaire based on ten learning media functions. Student’s perception was categorized in five responses, strongly agree, agree, agree enough, disagree, and strongly disagree. Result : The results of students perception based on media functions are media can attrack student’s attention (79,8%), media accelerates learning understanding (78,5%), media changes verbal message to clearer message (76,6%), media resolves space limitation problems (79,4%), media makes the learning process more communicative and effective (79,4%), media organizes learning time (78,5%), media eliminates student’s boredom (79,4%), media grows learning enthusiasm (72,1%), media can be used by students with different types of learning style (77%), and media makes the students more active (79,8%). Conclusion : Most of dental students of 2014 class in Muhammadiyah University of Yogyakarta agree that Kabanogi fulfill the ten learning media functions. Keywords : Active Learning, Dental Anatomy, Kartu Anatomi Gigi